Projected distribution of the westernmost subpopulation of Assamese macaques (Macaca assamensis pelops) under climate change: conservation implications of a threatened population - Khanal, Laxman; Upadhyaya, Laxmi Prasad; Pandey, Naresh; Chand, Dhirendra Bahadur; Karki, Melina; Chalise, Mukesh Kumar; Kyes, Randall C. (Frontiers in Conservation Science, 2023)
Anthropogenic climate change can have a negative impact on the distribution of habitat specialist species with narrow distributional ranges. Among the many areas around the world affected by climate change, the Himalayan region in particular is experiencing marked effects of global warming on its climatic patterns and life forms. This study assessed the current distribution of Assamese macaques (Macaca assamensis) in western Nepal, and projected their likely distribution (via habitat suitability modeling) for the years 2050 and 2070 under the two most plausible greenhouse gas emission scenarios (RCP4.5 and RCP6.0). We recorded a total of 159 Assamese macaques belonging to 10 groups (nine of them residing outside of protected area networks) between 684m and 2550m asl in western Nepal. Climatic niche modeling predicted that 37.03% (25,114 km2) of the total area of western Nepal (67,813 km2) represented suitable habitat of the species, the majority of which ranged between 1000 m and 2000 m asl. Future projections of the current climatic niche of the Assamese macaques revealed a consistent decrease in the suitable habitat for 2050 and 2070 in both of the greenhouse emission scenarios tested. With the RCP6.0 scenario, almost 57% of the current highly suitable habitat would be lost by 2070 with remaining suitable habitat shifted towards higher elevations. The loss of habitat directly affects the species survival and the range shift towards higher elevation exposes them to new areas for conflict with humans. Therefore, the Assamese macaque population in western Nepal requires a high conservation priority with the establishment of new protected areas.